(3GdGbJUGO GdQbej (B/s - (3GdehShj, UaGA YHO GdLHGQs; (3GdCYQLj, cGXe SYO s; (3RjfH gGOj fYegs ((3YeGf(B: s (3OGQ GdCjGe ddfTQ hGdJhRjY(B, s, 2017)
-(3GdGWGQ GdfXQj hGdeaGgjej(B:(3GdGWGQ GdeaGgjej ddGbJUGO GdQbej (B-(3bWGYGJ GdGbJUGO GdQbej (B-(3GdYdGbI Hjf GdGbJUGO GdQbej hGdJZjQGJ GdGbJUGO Gdcdj(B:(3GdYdGbI GdfXQjI Hjf eJZjQGJ GdGbJUGO GdQbej (B-(3JLQHI OhdI eGdjRjG aj GdGbJUGO GdQbej (B-(3JLQHI OhdI GdGeGQGJ GdYQHjI GdeJMOs
Keywords: (3GdGbJUGO GdQbejs